Assessing the potential for fall armyworm exchanges between the two American continents across the Mexico-Central America land bridge - Rodney N. Nagoshi; Edi A. Malo; Samuel Cruz-Esteban; Ninfa M. Rosas-García; Verónica Herrera-Mayorga; Robert L. Meagher (PLoS ONE, 2025)
The fall armyworm is a major agricultural pest of corn and multiple other crops. A native of the Western Hemisphere it is now a global concern after its discovery in Africa in 2016 and subsequent infestations in Asia and Australia. A defining characteristic of fall armyworm is its capacity for long distance migration, first documented for populations in North America and assumed to occur elsewhere. This trait increases the risk that phenotypes harmful to agriculture, such as pesticide resistance, that arise in one location can rapidly disseminate to even geographically distant populations. This study examines the extent to which the Mexico-Central America land bridge serves as a pathway for gene flow between the fall armyworm from the two American continents. The work builds on previous surveys in Mexico that suggest possible geographical or meteorological barriers limiting mass population movements. Fall armyworm collections from Mexico were analyzed for patterns of genetic variation and these were correlated with modeling of climate suitability, the locations of major corn production, and wind-dependent dispersal projections. Significant but transient genetic structure was found in Mexico consistent with climate suitability and air transport projections that support localized dispersal behavior rather than long-distance movements. The results indicate the movement of fall armyworm through Mexico does not involve migratory movements of mass populations as observed in the United States. This suggests that the exchange of fall armyworm between the two Americas across the Central America land bridge is limited in scope and frequency.